Screening for pathogenic neuronal autoantibodies in serum and CSF of patients with first-episode psychosis - Theorell, J; Ramberger, M; Harrison, R; Mgbachi, V; Jacobson, L; Waters, P; Erhardt, S; Sellgren, CM; Cervenka, S; Piehl, F; Irani, SR (Springer Nature, 2021)
Patients with autoimmune encephalitides, especially those with antibodies to the N-methyl-D-aspartate receptor (NMDAR), often present with prominent psychosis and respond well to immunotherapies. Although most patients progress to develop various neurological symptoms, it has been hypothesised that a subgroup of patients with first-episode psychosis (FEP) suffer from a forme fruste of autoimmune encephalitis. Without accurate identification, this immunotherapy-responsive subgroup may be denied disease-modifying treatments. Thirty studies addressing aspects of this hypothesis were identified in a systematic review. Amongst other shortcomings, 15/30 reported no control group and only 6/30 determined cerebrospinal fluid (CSF) autoantibodies. To ourselves address these-and other-limitations, we investigated a prospectively ascertained clinically well-characterised cohort of 71 FEP patients without traditional neurological features, and 48 healthy controls. Serum and CSF were tested for autoantibodies against seven neuronal surface autoantigens using live cell-based assays. These identified 3/71 (4%) patient sera with weak binding to either contactin-associated protein-like 2, the NMDAR or glycine receptor versus no binding from 48 control samples (p = 0.28, Fisher's test). The three seropositive individuals showed no CSF autoantibodies and no differences from the autoantibody-negative patients in their clinical phenotypes, or across multiple parameters of peripheral and central inflammation. All individuals were negative for CSF NMDAR antibodies. In conclusion, formes frustes of autoimmune encephalitis are not prevalent among FEP patients admitted to psychiatric care. Our findings do not support screening for neuronal surface autoantibodies in unselected psychotic patients.